2006
DOI: 10.2147/tcrm.2006.2.2.193
|View full text |Cite
|
Sign up to set email alerts
|

The management of glaucoma and intraocular hypertension: current approaches and recent advances

Abstract: Abstract:In the last decade, numerous novel ocular hypotensive agents have been introduced for the control of intraocular pressure (IOP). Clinicians now have more options than ever in the selection of medical therapy for the treatment of glaucoma and ocular hypertension. When selecting an ocular hypotensive medication for their patients, clinicians should consider not only the IOP-lowering efficacy of an agent, but also the ability of the drug to allow patients to achieve target levels of IOP that are low enou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 111 publications
0
27
0
Order By: Relevance
“…Finally, elevated intraocular pressure is one of several risk factors involved in the progression of glaucoma [157]. Using an animal model of ocular hypertension in which macrophages were systematically eliminated by treatment with clodronate liposomes, Huang et al [153] showed that inhibition of the JAK/STAT pathway was detrimental to retinal ganglion survival in vivo following acute experimentally-induced intraocular pressure elevation, but this response did not occur in the normal eye.…”
Section: The Visual Systemmentioning
confidence: 99%
“…Finally, elevated intraocular pressure is one of several risk factors involved in the progression of glaucoma [157]. Using an animal model of ocular hypertension in which macrophages were systematically eliminated by treatment with clodronate liposomes, Huang et al [153] showed that inhibition of the JAK/STAT pathway was detrimental to retinal ganglion survival in vivo following acute experimentally-induced intraocular pressure elevation, but this response did not occur in the normal eye.…”
Section: The Visual Systemmentioning
confidence: 99%
“…2 Glaucoma, a neurodegenerative disease of the retinal ganglion cells, is the second leading cause of blindness worldwide. 3 In the United States, 4 million people have glaucoma and 130 000 are legally blind from the disease. 3 In the Australian Blue Mountains Eye study of adults 49 years of age and older, the prevalence of open-angle glaucoma was 3% and OHT was found in 3.7% of participants.…”
Section: Introductionmentioning
confidence: 99%
“…3 In the United States, 4 million people have glaucoma and 130 000 are legally blind from the disease. 3 In the Australian Blue Mountains Eye study of adults 49 years of age and older, the prevalence of open-angle glaucoma was 3% and OHT was found in 3.7% of participants. 1 Control of IOP is important in patients with glaucoma: 4 a decrease of 1 mm Hg may lead to a 10% reduction in the risk of progressive nerve damage.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although several factors such as genetic predisposition, weakness of the optic nerve, severe myopia and thinness of the cornea have been identified to increase the risk of developing glaucoma, 3 one of the main risk factors is still considered to be elevated intra-ocular pressure (IOP). Therefore the available therapies for open angle glaucoma aim to lower the IOP in the anterior chamber of the eye by using various pharmaceuticals, laser trabeculoplasty or trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%